PENYUSUNAN SOAL HIGHER ORDER THINKING BAGI GURU PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR KECAMATAN CIGUDEG - Irman Sumantri (Universitas Gajah Putih, Indonesia, 2022)
This Community Service Program (PKM) is carried out with the aim of providing a conceptual understanding and implementation of the preparation of HOTS questions in the subject of Islamic religious education subjects in Cigudeg sub-district, Bogor district. The implementation of PKM is carried out by socialization and simulation methods. This activity is carried out by providing training and assistance in preparing HOTS-based questions in accordance with the guidelines for writing questions. The results obtained during socialization, that teachers understand conceptually and are able to prepare HOTS questions on the subject of Islamic religious education at the elementary school level. Thus, it can be concluded that, community service activities entitled the preparation of Higher Order Thinking Questions for Islamic religious education are running smoothly and effectively.